Enhanced thickness uniformity of large-scale α-Ga2O3 epilayers grown by vertical hot-wall mist chemical vapor deposition. Issue 4 (15th February 2022) - Park, Sun-Young; Ha, Minh-Tan; Kim, Kyoung-Ho; Van Lich, Le; Shin, Yun-Ji; Jeong, Seong-Min; Kwon, Se-Hun; Bae, Si-Young
Abstract: Smooth surface morphology and high thickness uniformity heteroepitaxy of corundum-structured ( α- ) gallium oxide (Ga2 O3 ) crystalline thin films on 100-mm diameter c -plane sapphire substrates were successfully demonstrated using vertical hot-wall mist chemical vapor deposition (CVD). The growth rate and surface morphology of the epitaxial layers were numerically and experimentally found to be dependent on the diameter of the precursor-diluted microdroplets approaching the substrate surface. Since the microdroplet is gradually evaporated while traveling through the furnace, the growth variables such as temperature, mist-flow velocity, and substrate position were tuned to obtain a suitable diameter of microdroplets approaching the substrate. In this study, the diameter of the approaching microdroplet was ≈2 μm, which was optimal for the smooth surface (root mean square roughness ≈1 nm) of α -Ga2 O3 epitaxial layers with a growth rate of ≈230 nm/h. Due to the even flow of mist in the vertical furnace, high thickness uniformity of the α -Ga2 O3 epitaxial layer is guaranteed on large-scale substrates, with a standard deviation of thickness as small as 28 nm, paving the way for highly reliable Ga2 O3 -based electric and optoelectronic devices.